New procedure for electronic deliveries in administrative proceedings - Cebera, Agata (Ius Novum, 2023)
This study focuses on the new procedure of electronic deliveries in administrative jurisdictional proceedings, as regulated by the provisions of the Code of Administrative Procedure. The primary research objective was to describe de lege lata the modes of individual deliveries, indicating their mutual hierarchy, while also addressing several issues related to the relationship between the Code and the Act on Electronic Deliveries. Both normative acts necessitate co-existence, and thus determining which of them and in which situational variants will be qualified as lex generali. This task is by no means facilitated by the fact that the characteristics of the framework regulation can be found in the Code, while the Act “model” regulates the rules of communication involving public entities. The main thesis presented in the study underscores the need for a systemic interpretation of the provisions of the latter Act. The author also believes that the definition of the scope of exclusions from the application of the Act was not designed appropriately. The issues raised have not been the subject of articles thus far.